Methods of Physical Recreation of Students Trained in Kickboxing Section - C. А. Пашкевич; Е. В. Крюков (OVS LLC, 2016)
Research objective: to evaluate the effectiveness of implementing sports massage in recreation of kickboxing students to improve their sports performance. Materials and methods. The research used: review and analysis of literature, pedagogical observations, physiological (relay test, strength endurance test, fatigue intensity assessment) and statistical methods. The participants of the research were three groups (5 persons in each group). The first group of students (C1) received preliminary warming massage (20 min), the second group (C2) received recreational massage after the training (20 min), the third group (C3) had passive rest before and after the training (20 min). Before and after the massage session, assessment of the response rate and strength endurance took place three times during the training (at the beginning, in the middle, and at the end) with regard to the level of the students' fatigue intensity during the training. For the rough evaluation of the cause-effect relationship between the influencing factor and the effect appearance, the research used the relative risk indicator (RR). Research results. The sports massage reduced the athletes' fatigue during the training (RR = 5.0, p < 0.05), i.e. the coach could increase the training load without any significant impact on the functional systems of the athletes. The preliminary massage had a more distinct positive effect on the students' response rate and endurance indicators. The recreational massage improved only the students' endurance processes during the training.